A calculated approach to nitrate bioremediation in temperature-variable mining environments: integrating adapted bacterial stimulation, carbon balancing, and hydraulic retention time - Potgieter, Gerhardus Petrus (Stellenbosch : Stellenbosch University, 2025)
Potgieter, Gerhardus Petrus. 2024. A calculated approach to nitrate bioremediation in temperature-variable mining environments: integrating adapted bacterial stimulation, carbon balancing, and hydraulic retention time. Unpublished doctoral dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131889